EARLY IDENTIFICATION AND BASIC LIFE SUPPORT FOR PNEUMOTHORAX - I Wayan Ade Punarbawa; Putu Pramana Suarjaya (Universitas Udayana, 2013)
Chest injury is one injury that often occurs and need immediate and precise handling that prevent people from death. Chest trauma 1/4 of the trauma that caused the death and 1/3 of those deaths occur in hospitals. One chest injury that often we get to the health center is pneumothorax. WHO declared in 2020 the level of morbidity and mortality from chest injuries will increase, to become the second leading cause of death in the world. From this data that need to know the signs and symptoms of peneumotoraks, identify the signs and symptoms so we can provide basic life support to the patient before the patient was referred to a medical center nearby so as to reduce the morbidity and mortality in patients with pneumothorax.